Israel and the politics of Jewish identity the secular religious impasse - Kohen, Asher 1936-1996; Zîser, Bārûḵ 1942- (Johns Hopkins Univ. Press, 2000)
"Since the 1980s, relationships between secular and religious Israelis have gone from bad to worse. What was formerly a politics of accommodation, one whose main objective was the avoidance of strife through "arrangements" and compromises, has become a winner-take-all, zero-sum game. The conflict is not over who gets what. Rather, it is a conflict over the very character of the polity, a struggle to define Israel's collective character. In Israel and the Politics of Jewish Identity Asher Cohen and Bernard Susser show how this transformation has been caused by structural changes in Israel's public sphere. Surveying many different levels of public life, they explore the change of Israel's politics from a dominant-party system to a balanced two-camp system. They trace the rise of the Haredi parties and the growing consonance of religiosity with right-wing politics." -- Book jacket.